IMPROVING STUDENTS’ ABILITY IN READING THROUGH GROUP DISCUSSION - Mintje, Intan; Maru, Mister Gidion; Kumayas, Tirza (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The purpose of this study is to determine whether or not the group discussions can improve students' ability to read. This study involved 23 students from class IX A at SMP Negeri 2 Tondano. This study is a quantitative research using pre-experimental design with pre-test and post-test design. Data from the pre-test and post-test were collected using multiple choice tests, both of which had 15 items. The findings of this study showed a significant difference in achievement between the pre-test and post-test. The highest pre-test score obtained by students was 60, while the highest post-test score obtained by students was 90. It can be concluded that the effect of group discussion can improve students' ability in reading at SMP Negeri 2 Tondano. In addition, students reported that group discussion helped them in improving each their ability to read well. This study recommends that the group discussion method can be used as a learning alternative in teaching reading especially in English reading to improve the ability of each student in school.